(untitled) (Research, Society and Development, 2021)
In times of social isolation, school activities live a new teaching format, requiring the efforts of an entire school team, where teachers and students seek alternatives for building knowledge and educational development in the hybrid mode. Therefore, the importance of continuing education for the improvement of methodologies and the use of new technologies in the teaching of mathematics is emphasized, systematically analyzing how the school space has helped at this time. This research aimed to analyze and reflect the development of mathematics teaching in the hybrid and remote modality in times of social isolation, as well as the initial and continuing teacher training and its necessary didactic skills. The methodology was based on the scientific search for articles, documents, e-books published in the last five years, using the Google Scholar platform. After reading the respective abstracts, 28 scientific articles were selected due to their importance to the educational context. The results revealed that the scientific production has been showing the importance for the use of new technologies in hybrid teaching, as well as the continuing education of the teacher with the insertion of new teaching proposals. Thus, the research points to the need for new studies, directing the reader to reflect on the teaching practice in relation to the use of new technologies. Because the reality shown does not show the existence of insertion, new pedagogical proposals, as well as accessibility to the demands that the new scenario in times of pandemic requires the implementation of hybrid and remote education in Brazilian education.